ChemInform Abstract: Synthesis of Some New Derivatives of Thiazolopyrimidines and Hydrolysis of Its Arylidene Derivative. Issue 35 (September 2015) - Nagarajaiah, H.; Khazi, Imtiyaz Ahmed M.; Begum, Noor Shahina
Abstract The synthesis of a variety of new derivatives of thiazolopyrimidine including tricyclic compound (XX) and some arylidene derivatives (III) is described.